FUNGSI PAJAK SEBAGAI SUMBER PENERIMAAN NEGARA : STUDI LITERATUR: bahasa indonesia - Amalia, Eri Sisca; Furqon, Imahda Khoiri (Journal of Financial and Tax, 2026)
Taxes are an important element in the management of state finances, serving as the main source of revenue to support national development and maintain economic stability. Taxes are not a financial responsibility of citizens, but also a strategic tool to encourage economic growth, equitable income distribution, and state financial capacity. This study reviews the role of taxes as a source of state revenue with an emphasis on two main points: problems in maximizing tax revenue and government efforts to improve the effectiveness of the taxation system. The problems faced include low compliance among taxpayers, alternatives for tax avoidance and fraud, suboptimal tax management, and the complexity of taxation in the digital economy era. The growth of the digital economy has made tax collection complicated because many transactions are difficult to track. In response, the government has reformed and modernized the tax system, including digitizing services, implementing a self-assessment system, integrating taxpayer data, and improving tax education and outreach programs for the public. This study applies a descriptive qualitative approach with a literature study method using secondary data from reliable sources. The findings show that taxes function not only as a source of government funding but also as a tool.